Band gap renormalization of diamondoids: vibrational coupling and excitonic effects. (29th November 2016) - Han, Peng; Bester, Gabriel
Abstract: We perform ab initio density functional theory calculations along with the frozen phonon approach to study the renormalization of the electronic structure of diamondoids induced by coupling to nuclear vibrations. We obtain an energy gap reduction between 0.1 and 0.3 eV across nine different diamondoids. The energy renormalization of the highest occupied molecular orbital state varies with the sizes and the symmetry of the diamondoids while that of the lowest unoccupied molecular orbital state is nearly constant. This behavior is explained using the localization of the electronic states. The energy gap renormalization is shown to originate mainly from bending C-H and rotation/shear H-C-H modes with frequencies between 800 and 1400 cm −1 . We calculate the band gap renormalization due to excitonic effects using a screened configuration interaction approach and find excitonic binding energies of around 2 eV in excellent agreement with experiment for our largest diamondoids.